MANAJEMEN RISIKO DAN STRATEGIC CONTROL DALAM TATA KELOLA ASURANSI UMUM - Napitupulu, Reimond Hasangapan Mikkael; Sardjito, R. Muh Deddy Hanif; Romdaniyah, Romdaniyah (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the contribution of risk management and strategic control in enhancing the effectiveness of corporate governance in the general insurance industry. Strong corporate governance is a key prerequisite for addressing risk complexity, regulatory requirements, and the competitive dynamics of the insurance sector. This study adopts a qualitative approach using a systematic literature review and descriptive analysis of risk management frameworks, strategic control mechanisms, and corporate governance practices in general insurance companies. Data were obtained from secondary sources, including reputable international journal articles, industry regulations, and relevant corporate reports. The findings indicate that the integration of comprehensive risk management with effective strategic control strengthens oversight functions, improves the quality of strategic decision making, and promotes the implementation of transparency, accountability, and responsibility principles. These findings confirm that the synergy between risk management and strategic control plays a significant role in improving corporate governance quality and supporting the sustainability of general insurance companies’ performance.